Sodium bismuth titanate-based leadless piezoelectric textured ceramic and preparation method thereof

By adopting specific chemical composition and preparation methods in sodium bismuth titanate-based lead-free piezoelectric ceramics, the problem that ceramics are difficult to achieve high texture, density and purity in the prior art is solved, and the ideal electrical properties and excellent piezoelectric properties of the ceramics are achieved.

CN119613110AActive Publication Date: 2025-03-14SUN YAT SEN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510008741.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-03-14
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Existing lead-free piezoelectric ceramics cannot achieve high texture, density and purity while maintaining ideal electrical properties.

Method used

The chemical composition of the bismuth titanate-based lead-free piezoelectric textured ceramic is [Bi0.5(Na0.82K0.18)0.5]0.96Sr0.04Ti1-xTaxO3. The bismuth titanate template grains were prepared through a single molten salt system, and the reaction template grain growth method and casting molding process were used to improve the texture and grain orientation of the ceramic.

Benefits of technology

It achieves the improvement of the texture, density and high purity of the ceramic while maintaining ideal electrical properties, which significantly improves its piezoelectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613110A_ABST
    Figure CN119613110A_ABST
Patent Text Reader

Abstract

The invention provides a sodium bismuth titanate-based leadless piezoelectric textured ceramic and a preparation method thereof. The chemical composition of the sodium bismuth titanate-based leadless piezoelectric textured ceramic is [Bi < 0.5 > (Na < 0.82 > K < 0.18 >) < 0.5 >] < 0.96 > Sr < 0.04 > Ti < 1-x > Ta < x > O < 3, 0 lt >, xlt; 0.01, and the texture degree of the sodium bismuth titanate-based leadless piezoelectric texture ceramic is gt; 90%. According to the lead-free piezoelectric textured ceramic, grain height orientation is achieved, the remanent polarization of the lead-free piezoelectric textured ceramic is greatly improved through grain height orientation, and therefore the piezoelectric performance is improved, and the lead-free piezoelectric textured ceramic is anisotropic piezoelectric ceramic with the excellent piezoelectric performance. The invention also provides a preparation method of the sodium bismuth titanate-based leadless piezoelectric textured ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a sodium bismuth titanate-based lead-free piezoelectric textured ceramic and a preparation method thereof. Background Art

[0002] As a material that can realize the mutual conversion between electrical energy and mechanical energy, piezoelectric ceramics are widely used in many fields such as brakes and micro-displacers due to their large electric field induced strain. Although lead-based piezoelectric ceramics have advantages in electrical properties and stability, the toxicity and environmental hazards of lead oxide, its main raw material, have prompted researchers to seek lead-free alternative materials.

[0003] Bismuth sodium titanate-based lead-free piezoelectric ceramics have attracted attention due to their superior electrostrain and high Curie temperature. However, their performance is not yet comparable to that of lead-based materials, so there is an urgent need to improve their application potential through modification and optimization. Common modification methods include multi-component solid solution, ion doping and improvement of preparation process. Among them, multi-component solid solution introduces components with different perovskite structures to form a solid solution with bismuth sodium titanate-based lead-free piezoelectric ceramics, forming a quasi-modular phase boundary, obtaining quasi-modular phase boundary characteristics, greatly improving its electrical properties, and thus improving piezoelectric properties. Ion doping introduces rare earth elements or low-melting-point elements to change the crystal structure and improve electrical properties. The orientation of grains is closely related to the piezoelectric properties of the material. Randomly oriented polycrystalline ceramics can be prepared by texturing technology to orient their grains, showing that they have better performance in a specific direction. At present, grain orientation technology is the most commonly used method for preparing textured ceramics. The purpose of grain orientation can be achieved by adding template grains and tape casting.

[0004] However, the existing lead-free piezoelectric ceramics cannot have ideal electrical properties while maintaining high texture, density and high purity. Therefore, a new lead-free piezoelectric ceramic still needs to be developed. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a sodium bismuth titanate-based lead-free piezoelectric textured ceramic, which has ideal electrical properties while maintaining high texture, density and high purity.

[0006] The invention also provides a method for preparing sodium bismuth titanate-based lead-free piezoelectric textured ceramics.

[0007] The first aspect of the present invention provides a sodium bismuth titanate-based lead-free piezoelectric textured ceramic, the chemical composition of which is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr0.04 Ti 1-x Ta x O3, where 0 < x < 0.01, and the texture degree of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic is > 90%.

[0008] One technical solution in the technical solution of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic of the present invention has at least the following beneficial effects:

[0009] The sodium bismuth titanate-based lead-free piezoelectric textured ceramic of the present invention has highly oriented grains. The high orientation of the grains is beneficial to greatly improving its remanent polarization intensity, thereby improving the piezoelectric performance. It is an anisotropic piezoelectric ceramic with excellent piezoelectric performance. It can have ideal electrical properties while maintaining a high texture degree, density, and high purity.

[0010] According to some embodiments of the present invention, the preferred range of x is 0.003 < x < 0.009.

[0011] According to some embodiments of the present invention, the textured ceramic grains of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic are oriented along <001>.

[0012] According to some embodiments of the present invention, x is 0.006, and the chemical composition of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3.

[0013] [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3 lead-free piezoelectric textured ceramic has a higher electrostrictive strain performance in randomly oriented ceramics. Therefore, the texture technology is used to further improve the performance of this ceramic.

[0014] The second aspect of the present invention provides a method for preparing the sodium bismuth titanate-based lead-free piezoelectric textured ceramic of the first aspect of the present invention, including the following steps:

[0015] ​​Bismuth titanate template crystals are prepared by a single molten salt system. According to the chemical composition, the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, strontium carbonate and tantalum pentoxide are weighed and mixed with bismuth oxide, additives and solvents to obtain a ceramic slurry. The ceramic slurry is tape-casted by a reactive template grain growth method through a tape-casting process to obtain a single-layer tape-cast film. The single-layer tape-cast films are stacked to obtain a tape-cast membrane sheet. The tape-cast membrane sheet is sequentially subjected to hot pressing, primary cold isostatic pressing, debinding, secondary cold isostatic pressing and sintering to obtain the sodium bismuth titanate-based lead-free piezoelectric textured ceramic.

[0016] The present invention provides a technical solution in a method for preparing sodium bismuth titanate-based lead-free piezoelectric textured ceramics, which has at least the following beneficial effects:

[0017] When researchers prepare piezoelectric textured ceramics with high electrostrain, if the molten salt method is used to prepare bismuth titanate template grains, the bismuth titanate template grains are usually prepared using a sodium chloride-potassium chloride (NaCl-KCl) composite molten salt system. The prepared grains vary in size, and because the preparation temperature is high, a certain amount of impurities will be contained in the template grains, thereby affecting the stoichiometric ratio of the textured ceramics. Therefore, the final bismuth titanate template grains have a relatively small direction, contain impurities, and have a large size span, and it is impossible to prepare high-purity and large-sized flaky bismuth titanate template grains. In order to obtain high-purity lead-free piezoelectric ceramics that can improve electrical properties through doping modification while maintaining a high texture and density, the preparation process needs to be further optimized. The present invention is based on further improving BNKT (full name is (Bi 0.5 Na 0.84 K 0.16 ) 0.5 TiO3-0.45(Bi 0.1 Sr 0.85 The piezoelectric properties of TiO3-based ceramics were improved by co-doping A-site and B-site ions in the binary solid solution of sodium bismuth titanate-potassium bismuth titanate (BNT-BKT). Through a single molten salt system, combined with texturing technology (reaction template grain growth method), a suitable template and casting process were used to change the ceramic crystal structure, so that the ceramic grains were arranged in an orderly manner, thereby obtaining anisotropic piezoelectric ceramics with excellent piezoelectric properties. It can provide a reference for the industry to prepare template grains and textured ceramics, and further promote the practical application of lead-free piezoelectric ceramics.

[0018] The preparation method of the present invention uses a sheet-shaped doped bismuth titanate with the same composition as the doped sodium bismuth titanate ceramic powder as a template. Since the reaction template grain growth method is to mix the template and the drug powder together, stack them and then sinter them, during the sintering process, the template grains engulf the surrounding drug powder and participate in the reaction, so the same composition can avoid the template grains engulfing the surrounding drug powder particles to participate in the reaction, and the formed part will have internal stress caused by different lattice constants, thereby avoiding the influence of internal stress on piezoelectric performance.

[0019] The preparation method of the present invention has simple process, easy operation and low cost, and can save experimental cost and equipment investment.

[0020] According to some embodiments of the present invention, the bismuth titanate template crystal is in the form of a sheet, and the chemical formula is Bi4Ti3O 12 .

[0021] Bismuth titanate template crystals are the most commonly used template grains in the preparation of BNT-based textured ceramics by the RTGG method because of their lamellar structure, good thermal stability, and BNT-related elements. Bismuth titanate template grains are pre-arranged or distributed in a specific orientation. When other reactants (such as precursor powders) are introduced and chemical reactions occur, the newly formed BNT-based phase will grow along the orientation of the bismuth titanate template grains, thereby improving the overall texture of the ceramic material. Bismuth titanate itself may participate in the chemical reaction and be converted into part of the BNT-based phase through processes such as solid-phase reaction and liquid-phase sintering, while retaining its original texture. Because textured ceramics have a more consistent crystal orientation, they tend to exhibit better electrical, mechanical, and other physical properties.

[0022] According to some embodiments of the present invention, the method for preparing the bismuth titanate template crystal comprises the following steps: after mixing Bi2O3 and TiO2, adding a single molten salt, and after ball milling, drying and calcining, obtaining the bismuth titanate template crystal.

[0023] According to some embodiments of the present invention, the single molten salt is a KCl molten salt system.

[0024] According to some embodiments of the present invention, the method for preparing the bismuth titanate template crystal may be:

[0025] First, Bi2O3 and TiO2 are reacted according to the chemical reaction equation 2Bi2O3+3TiO2→Bi4Ti3O 12 Formula calculation is performed, bismuth oxide and titanium dioxide are weighed and mixed according to the molar ratio, a single potassium chloride (KCl) molten salt is selected for the molten salt system, and the mass ratio of the molten salt (KCl) to the reaction raw materials (Bi2O3 and TiO2) can be 1.5:1.

[0026] After weighing, place it in a ball mill, use zirconium oxide balls as grinding balls, anhydrous ethanol as solvent, and mix it in a planetary ball mill at 300r / min for 4h. The obtained slurry is dried at 80℃, and the powder obtained after drying is placed in a corundum crucible, covered with a crucible cover, sealed and placed in a muffle furnace for synthesis to prevent the molten salt and Bi element from volatilizing in large quantities at high temperatures. The synthesis process is to heat to 1140℃ at a heating rate of 5℃ / min at room temperature for 8h, then cool to 300℃ at a rate of 3℃ / min and then cool with the furnace. The synthesized powder is added to deionized water at 80-100℃ for stirring, dispersion and washing multiple times. After pouring off the upper clear liquid, the powder in the beaker is finally dried to obtain the flaky Bi4Ti3O prepared in a pure KCl system. 12 Template grains.

[0027] According to some embodiments of the invention, the additive comprises polyvinyl butyral, dibutyl phthalate, polyethylene glycol and castor oil.

[0028] According to some embodiments of the present invention, the mass of castor oil accounts for 1-3% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0029] According to some embodiments of the present invention, the mass of castor oil accounts for any value of 1%, 1.5%, 2%, 2.5%, 3% of the total mass of bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide, or a range formed by any two of them, such as 1.5-2.5%.

[0030] According to some embodiments of the present invention, the mass of castor oil accounts for 2% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0031] According to some embodiments of the present invention, the mass of polyvinyl butyral accounts for 8-10% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0032] According to some embodiments of the present invention, the mass of polyvinyl butyral accounts for any value of 8%, 8.5%, 9%, 9.5%, 10% of the total mass of bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide, or a range formed by any two of them, such as 8 to 10%.

[0033] According to some embodiments of the present invention, the mass of polyvinyl butyral accounts for 9% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0034] According to some embodiments of the present invention, the mass of dibutyl phthalate accounts for 9-12% of the total mass of the bismuth titanate template crystal, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0035] According to some embodiments of the present invention, the mass of dibutyl phthalate accounts for any value of 9%, 10%, 11%, 12% of the total mass of bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide, or a range formed by any two of them, such as 10-12%.

[0036] According to some embodiments of the present invention, the mass of dibutyl phthalate accounts for 10% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0037] According to some embodiments of the present invention, the solvent is anhydrous ethanol, wherein the mass of the solvent accounts for 50-70% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0038] According to some embodiments of the present invention, the solvent is anhydrous ethanol, wherein the mass of the solvent accounts for any value of 55%, 60%, 65%, 70% or a range formed by any two of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide, such as 60-65%.

[0039] According to some embodiments of the present invention, the solvent is anhydrous ethanol, wherein the mass of the solvent accounts for 60% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0040] According to some embodiments of the present invention, a double scraper can be used during tape casting. The height of the double scraper needs to be controlled. If it is too low, the degree of orientation of the template grains will increase, but the degree of increase is limited and the scraping efficiency is not high. If it is too high, the degree of orientation of the template grains will decrease, the texture of the ceramic will decrease, and the piezoelectric performance will deteriorate.

[0041] According to some embodiments of the present invention, the stacking method comprises: laminating and pressing two single-layer cast films at 80° C. to make them fit tightly together, and repeating the operation to stack multiple cast films to a thickness of 2 to 3 mm.

[0042] According to some embodiments of the present invention, the hot pressing comprises: hot pressing at 60-80° C. and 50-60 MPa for 15-20 min.

[0043] According to some embodiments of the present invention, the debinding procedure includes: heating to 240°C at room temperature for 120 minutes, heating to 350°C for 270 minutes, and then heating to 600°C for 500 minutes, keeping warm for 80 minutes, and then cooling with the furnace.

[0044] According to some embodiments of the present invention, the primary cold isostatic pressing comprises: maintaining pressure at 200-250 MPa for 5-10 min; and / or, the secondary cold isostatic pressing comprises: maintaining pressure at 200-250 MPa for 5-10 min.

[0045] According to some embodiments of the present invention, the sintering includes: heating to 1150° C. at a rate of 3-5° C. / min and then keeping the temperature for 8 hours.

[0046] According to some embodiments of the present invention, the sintering is performed using a double-layer alumina crucible and a homogeneous powder burying method.

[0047] According to some embodiments of the present invention, bismuth oxide, titanium dioxide, potassium chloride and anhydrous ethanol are placed in a ball mill, and ball milled for 4 hours at a speed of 300 r / min using a planetary ball mill. The mixed powder is dried, then loaded into a crucible and placed in a muffle furnace for calcination, and the temperature is increased to 1140° C. at a rate of 5° C. / min and kept warm for 8 hours.

[0048] According to some embodiments of the present invention, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide, bismuth oxide, additives and solvents are mixed, ball-milled at a speed of 300 r / min for 12 hours, bismuth titanate template grains are added, and ball-milled at a speed of 250 r / min for 12 hours to obtain a ceramic slurry.

[0049] According to some embodiments of the present invention, the ceramic slurry is defoamed by a defoamer, and then a plastic film is laid on the casting base tape. After the double scraper device is assembled, the material trough and the scraper device are placed, and the height of the double scraper is set with a micrometer. The front blade is used to cast the slurry once, so that the slurry is initially spread on the casting base tape, and the distance between it and the casting base tape is 500μm. The rear blade is used to cast the slurry after spreading for a second time, in order to make the final single-layer casting film smoother and the grain arrangement more orderly, and the distance between it and the casting base tape is 500μm. The drying device of the casting machine is turned on and set to 50°C, and the appropriate initial speed of the casting machine is set. Then, the casting slurry is poured into the material trough. After the slurry is completely poured into the material trough, the forward rotation of the casting molding machine is turned on, so that the slurry is spread on the casting film base tape. After the casting is completed, wait for 5 to 10 minutes, and after the solvent of the casting film is dried, a single-layer casting film with a thickness of about 40μm is obtained.

[0050] Lamination is to laminate two single-layer cast films at 70-80℃ and press them to make them fit tightly. Repeat the operation to laminate multiple cast films to a thickness of 2-3mm, then hot press at 60-80℃ and 50-60MPa for 15-20min, and then perform cold isostatic pressing once, and keep the pressure at 200-250MPa for 5-10min to obtain a cast film sheet. The purpose is to make the cast films fit more tightly and improve the density.

[0051] According to some embodiments of the present invention, bismuth oxide is 3% of the mole fraction of the bismuth titanate template crystal.

[0052] According to some embodiments of the present invention, after sintering, both sides of the ceramic sample are polished, silver-plated and polarized. After the polarization is completed, a textured ceramic that can be tested is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is Bi4Ti3O sintered at 1140℃ for 8h in pure salt KCl system. 12 XRD diffraction pattern of template particles.

[0054] Figure 2 The improved textured ceramic-Sr prepared in Example 1 0.004 Ta 0.006 and the randomly oriented ceramic-Sr prepared in Comparative Example 2 0.004 Ta 0.006 XRD diffraction pattern.

[0055] Figure 3 The unmodified textured ceramic-Sr prepared in Example 1 0.004 Ta 0.006 and the randomly oriented ceramic-Sr prepared in Comparative Example 2 0.004 Ta 0.006 XRD diffraction pattern.

[0056] Figure 4 It is Bi4Ti3O sintered at 1140℃ for 8h in pure salt KCl system. 12 Scanning electron microscope (SEM) image of template grains.

[0057] Figure 5 It is Bi4Ti3O sintered at 1100℃ for 2h in a mixed salt NaCl-KCl system. 12 Scanning electron microscope (SEM) image of template grains.

[0058] Figure 6 This is a microscopic morphology of the cross section of the textured ceramic prepared in Example 1.

[0059] Figure 7 The improved textured ceramic-Sr prepared in Example 10.004 Ta 0.006 Electrostrictive curve

[0060] Figure 8 is the unmodified textured ceramic - Sr prepared in Comparative Example 1 0.004 Ta 0.006 Electrostrictive curve Detailed implementation manners

[0061] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in combination with the embodiments, but the present invention is not limited to these embodiments

[0062] In a first aspect, in some embodiments of the present invention, a sodium bismuth titanate - based lead - free piezoelectric textured ceramic is provided, with a chemical composition of [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 0.96 Sr 0.04 Ti 1x Ta x O3, 0 < x < 0.01, and the texture degree of the sodium bismuth titanate - based lead - free piezoelectric textured ceramic > 90%

[0063] It should be noted that for the sodium bismuth titanate - based lead - free piezoelectric textured ceramic of the present invention, the grains are highly oriented. The high orientation of the grains is beneficial to greatly improving its remanent polarization intensity, thereby improving the piezoelectric performance. It is an anisotropic piezoelectric ceramic with excellent piezoelectric performance

[0064] Combined with the first aspect, in some embodiments of the present invention, the textured ceramic grains of the sodium bismuth titanate - based lead - free piezoelectric textured ceramic are oriented along <001>

[0065] It should be noted that the textured ceramic grains of the lead - free piezoelectric textured ceramic are oriented along <001>, and the texture degree is greater than 90%, which has the following several important beneficial effects

[0066] 1. Enhanced piezoelectric performance

[0067] The grain arrangement oriented along <001> can significantly improve the piezoelectric response of the material, usually showing a significantly increased piezoelectric coefficient (d33). The piezoelectric effect is usually closely related to the orientation of the grains. In particular, the grains oriented along the <001> direction can optimize the polarization effect of the material, thereby enhancing its piezoelectric performance. A well - oriented material can effectively convert mechanical energy into electrical energy (reverse piezoelectric effect), or convert electrical energy into mechanical energy (forward piezoelectric effect)

[0068] ​Due to the high texture degree (>90%), most of the grains are oriented in the same direction, which will further improve the output of the piezoelectric effect and enhance the piezoelectric coefficient of the material, making it show higher efficiency in practical applications.

[0069] 2. Improved the mechanical properties of materials:

[0070] A high degree of texture usually means that the orientation of the grains inside the material is very consistent. This structure not only improves the piezoelectric performance, but also enhances the mechanical strength and toughness of the material. Ceramic materials with a higher degree of texture usually have better crack resistance and deformation resistance than non-textured materials. The uniform grain structure of textured ceramics contributes to the durability and stability of the material during use, especially exhibiting excellent mechanical properties under high loads and long-term use.

[0071] 3. Improved motor conversion efficiency:

[0072] Due to the directional preference of textured ceramic grains ( <001> ), so that the electric field can propagate more efficiently between the grains, enhancing the material's motor conversion efficiency. This is crucial for piezoelectric applications that require efficient energy conversion (such as sensors, drives, etc.). This orientation can also optimize the polarization behavior of piezoelectric ceramics under the action of an electric field, thereby improving its power density and response speed in practical applications.

[0073] 4. Optimized the stability and consistency of materials:

[0074] High texture ensures the uniformity of the crystal structure of the material, which is crucial to the long-term stability of the material. Textured ceramics can maintain their performance stability and avoid performance degradation under environmental changes such as temperature fluctuations, external stress or electric field changes. The grain directionality of textured ceramics is strong, which can effectively reduce the influence of grain boundary defects, thereby improving the consistency and reliability of the material.

[0075] 5. Reduce energy loss and improve high temperature resistance:

[0076] <001> Oriented grains make the ceramic's response to an applied electric field more precise and efficient, and the material can efficiently convert external energy. High texture helps reduce defects and domain wall motion inside the material, thereby reducing dielectric loss. Usually it has good stability in high temperature environments. Therefore, ceramics with good orientation can maintain their piezoelectric properties at high temperatures and are suitable for applications in high temperature or complex environments.

[0077] These effects make the material have excellent performance in piezoelectric applications (such as sensors, actuators, energy harvesting, acoustic devices, etc.) and meet the requirements of sustainable development.

[0078] In combination with the first aspect, in some embodiments of the present invention, x is 0.006, and the chemical composition of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3.

[0079] [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3 lead-free piezoelectric textured ceramics have high electrostrain performance among randomly oriented ceramics, so the performance of the ceramics can be further improved by using texturing technology.

[0080] In a second aspect, in some embodiments of the present invention, there is provided a method for preparing the sodium bismuth titanate-based lead-free piezoelectric textured ceramic of the first aspect of the present invention, comprising the following steps:

[0081] Bismuth titanate template crystals are prepared by a single molten salt system. According to the chemical composition, bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, strontium carbonate and tantalum pentoxide are weighed and mixed with bismuth oxide, additives and solvents to obtain a ceramic slurry. The ceramic slurry is tape-casted by a reactive template grain growth method through a tape-casting process to obtain a single-layer tape-cast film. The single-layer tape-cast films are stacked to obtain a tape-cast membrane sheet. The tape-cast membrane sheet is sequentially subjected to hot pressing, primary cold isostatic pressing, debinding, secondary cold isostatic pressing and sintering to obtain the sodium bismuth titanate-based lead-free piezoelectric textured ceramic of the present invention.

[0082] When researchers prepare piezoelectric textured ceramics with high electrostrain, if the molten salt method is used to prepare bismuth titanate template grains, the bismuth titanate template grains are usually prepared using a sodium chloride-potassium chloride (NaCl-KCl) composite molten salt system. The prepared grains vary in size, and because the preparation temperature is high, a certain amount of impurities will be contained in the template grains, thereby affecting the stoichiometric ratio of the textured ceramics. Therefore, the final bismuth titanate template grains have a relatively small direction, contain impurities, and have a large size span, and it is impossible to prepare high-purity and large-sized flaky bismuth titanate template grains. In order to obtain high-purity lead-free piezoelectric ceramics that can improve electrical properties through doping modification while maintaining a high texture and density, the preparation process needs to be further optimized. The present invention is based on further improving BNKT (full name is (Bi 0.5 Na 0.84 K 0.16 ) 0.5TiO3-0.45(Bi 0.1 Sr 0.85 The piezoelectric properties of TiO3-based ceramics were improved by co-doping A-site and B-site ions in the binary solid solution of sodium bismuth titanate-potassium bismuth titanate (BNT-BKT). Through a single molten salt system, combined with texturing technology (reaction template grain growth method), a suitable template and casting process were used to change the ceramic crystal structure, so that the ceramic grains were arranged in an orderly manner, thereby obtaining anisotropic piezoelectric ceramics with excellent piezoelectric properties. It can provide a reference for the industry to prepare template grains and textured ceramics, and further promote the practical application of lead-free piezoelectric ceramics.

[0083] It can be understood that the preparation method of the present invention uses the flake doped bismuth titanate with the same composition as the doped sodium bismuth titanate ceramic powder as a template. Since the reaction template grain growth method is to mix the template and the powder together, stack them and then sinter them, during the sintering process, the template grains engulf the surrounding powder and participate in the reaction, so the same composition can avoid the template grains engulfing the surrounding powder particles to participate in the reaction, and the formed part will have internal stress caused by different lattice constants, thereby avoiding the influence of internal stress on piezoelectric properties.

[0084] The preparation method of the present invention has simple process, easy operation and low cost, and can save experimental cost and equipment investment.

[0085] In combination with the second aspect, in some embodiments of the present invention, the bismuth titanate template crystal is in the form of a sheet, and the chemical formula is Bi4Ti3O 12 .

[0086] Bismuth titanate template crystals are flake-shaped and can bring a series of beneficial effects to ceramic materials, including the following advantages:

[0087] The flake template grains can provide a preferred direction, so that in the subsequent synthesis process, the sodium bismuth titanate-based ceramic crystals tend to grow along the direction of the flake template grains, which helps to improve the grain orientation of the ceramic and greatly improve the texture of the final textured ceramic. For sodium bismuth titanate-based ceramics, the highly textured microstructure formed by the flake template grains usually brings better electrical properties, such as higher dielectric constant, lower dielectric loss and stronger piezoelectric response, which are important characteristics pursued by high-performance electronic components.

[0088] The presence of flake template grains can guide the crystals to grow in a specific direction, reduce microcracks and other internal defects caused by random orientation, and improve the overall mechanical strength of the material. By using flake template grains, the particle size and spatial distribution in the final ceramic material can be better controlled, thereby obtaining a textured ceramic with good density and flatness.

[0089] In combination with the second aspect, in some embodiments of the present invention, the preparation method of bismuth titanate template crystals includes the following steps: after mixing Bi2O3 and TiO2, adding a single molten salt, and obtaining bismuth titanate template crystals after ball milling, drying and calcination.

[0090] According to some embodiments of the present invention, the single molten salt is a KCl molten salt system.

[0091] Compared with the single NaCl system, the template generated by the KCl system has high crystallinity and high purity. Figure 1 It can also be seen from the XRD pattern that the diffraction peaks in the XRD pattern of the BiT template crystals prepared using the KCl molten salt system are completely consistent with the BiT of PDF#72-1019 on the standard PDF card. + As an impurity, it enters the BiT crystal and easily forms Na 0.5 Bi 4.5 Ti4O 15 , and then by Bi4Ti3O 12 The three-layer TiO6 oxygen octahedron and Na 0.5 Bi 4.5 Ti4O 15 Four-layer TiO6 oxygen octahedron in (Bi2O2) 2+ The layers are arranged alternately to form a superlattice structure, forming a symbiotic Na 0.5 Bi 8.5 Ti7O 27 , resulting in the low purity of the prepared BiT template, making it difficult to calculate the specific phase content, and the stoichiometric ratio of the prepared textured ceramic is offset, affecting the performance of the sample. Therefore, the present invention selects a KCl molten salt system to prepare BiT template grains.

[0092] According to some embodiments of the present invention, the method for preparing bismuth titanate template crystals may be:

[0093] First, Bi2O3 and TiO2 are reacted according to the chemical reaction equation 2Bi2O3+3TiO2→Bi4Ti3O 12 Formula calculation is performed, bismuth oxide and titanium dioxide are weighed and mixed according to the molar ratio, a single potassium chloride (KCl) molten salt is selected for the molten salt system, and the mass ratio of the molten salt (KCl) to the reaction raw materials (Bi2O3 and TiO2) can be 1.5:1.

[0094] After weighing, place it in a ball mill, use zirconium oxide balls as grinding balls, anhydrous ethanol as solvent, and mix it in a planetary ball mill at 300r / min for 4h. The obtained slurry is dried at 80℃, and the powder obtained after drying is placed in a corundum crucible, covered with a crucible cover, sealed and placed in a muffle furnace for synthesis to prevent the molten salt and Bi element from volatilizing in large quantities at high temperatures. The synthesis process is to heat to 1140℃ at a heating rate of 5℃ / min at room temperature for 8h, then cool to 300℃ at a rate of 3℃ / min and then cool with the furnace. The synthesized powder is added to deionized water at 80-100℃ for stirring, dispersion and washing multiple times. After pouring off the upper clear liquid, the powder in the beaker is finally dried to obtain the flaky Bi4Ti3O prepared in a pure KCl system. 12 Template grains.

[0095] In conjunction with the second aspect, in some embodiments of the present invention, the additive includes polyvinyl butyral, dibutyl phthalate, polyethylene glycol and castor oil.

[0096] The role of polyvinyl butyral is to act as a binder, forming a network structure in the slurry, combining ceramic powder particles together, increasing the viscosity of the slurry, ensuring the uniformity of the slurry throughout the entire processing process, and helping to prepare a smooth cast film. At the same time, it provides the necessary mechanical strength for the green body, making it less likely to break and ensuring the dimensional accuracy of the ceramic sheet.

[0097] The role of dibutyl phthalate is to act as a plasticizer to prevent powder particles from agglomerating and maintain the stability of the slurry. Dibutyl phthalate weakens the interaction between molecules by inserting between polymer chains, making the slurry have good fluidity and processability at lower temperatures.

[0098] The role of polyethylene glycol is to act as a plasticizer, which can improve the fluidity of the slurry by reducing its viscosity, making the slurry suitable for casting and easier to spread into a uniform thin layer. It also has a lubricating effect, helping the cast film and green body to be smoothly separated from the mold or carrier, reducing the risk of damage during demolding. Polyethylene glycol has a slow volatilization rate, which can provide a longer time window before sintering to maintain the plasticizing effect, and is easier to completely decompose during high-temperature sintering, leaving no harmful residues, and is more environmentally friendly.

[0099] Castor oil acts as a dispersant. When preparing tape casting slurry, powder particles tend to agglomerate, which affects the uniformity of the slurry and the performance of the final textured ceramic. Castor oil can be adsorbed on the surface of particles, changing the surface properties of particles and reducing the attraction between particles, thereby preventing the agglomeration of powder particles. At the same time, it helps to maintain a stable suspension state of ceramic powder in the solvent, increase the viscosity of the slurry, and make it difficult for particles to settle or stratify.

[0100] In combination with the second aspect, in some embodiments of the present invention, the mass of castor oil accounts for 2% of the total mass, the mass of polyvinyl butyral accounts for 9% of the total mass, and the mass of dibutyl phthalate accounts for 10% of the total mass.

[0101] In combination with the second aspect, in some embodiments of the present invention, the solvent is anhydrous ethanol, wherein the mass of the solvent accounts for 60% of the total mass of the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide.

[0102] In combination with the second aspect, in some embodiments of the present invention, a double scraper can be used during tape casting. The height of the double scraper needs to be controlled. If it is too low, the degree of orientation arrangement of the template grains will increase, but the degree of increase is limited and the scraping efficiency is not high. If it is too high, the degree of orientation arrangement of the template grains will decrease, the texture of the ceramic will decrease, and the piezoelectric performance will deteriorate.

[0103] In combination with the second aspect, in some embodiments of the present invention, the stacking method includes: laminating and pressing two single-layer cast films at 80° C. to make them fit tightly, and repeating the operation to stack multiple cast films to a thickness of 2 to 3 mm.

[0104] In combination with the second aspect, in some embodiments of the present invention, hot pressing includes: hot pressing at 70° C. and 60 MPa for 20 min.

[0105] In combination with the second aspect, in some embodiments of the present invention, the debinding procedure includes: heating to 240°C after 120 minutes at room temperature, heating to 350°C after 270 minutes, and then heating to 600°C after 500 minutes, keeping warm for 80 minutes and then cooling with the furnace.

[0106] In combination with the second aspect, in some embodiments of the present invention, the primary cold isostatic pressing includes: maintaining pressure at 200 MPa for 5 minutes.

[0107] In combination with the second aspect, in some embodiments of the present invention, the secondary cold isostatic pressing includes: maintaining the pressure at a pressure of 200 to 250 MPa for 5 to 10 minutes.

[0108] In combination with the second aspect, in some embodiments of the present invention, sintering includes: heating to 1150° C. at a rate of 5° C. / min and then keeping the temperature for 8 hours.

[0109] In combination with the second aspect, in some embodiments of the present invention, a double-layer alumina crucible is used for sintering and a homogeneous powder burying method is used for sintering.

[0110] In combination with the second aspect, in some embodiments of the present invention, bismuth oxide, titanium dioxide, potassium chloride and anhydrous ethanol are placed in a ball mill and ball milled at a speed of 300 r / min for 4 hours using a planetary ball mill. The mixed powder is dried, then loaded into a crucible and placed in a muffle furnace for calcination, and the temperature is raised to 1140°C at a rate of 5°C / min and kept warm for 8 hours.

[0111] In combination with the second aspect, in some embodiments of the present invention, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide, bismuth oxide, additives and solvents are mixed, ball-milled at a speed of 300 r / min for 12 hours, bismuth titanate template grains are added, and ball-milled at a speed of 250 r / min for 12 hours to obtain a ceramic slurry.

[0112] In combination with the second aspect, in some embodiments of the present invention, a debubbler is used to debubble the ceramic slurry, and then a plastic film is laid on the casting base tape. After the double scraper device is assembled, the material trough and the scraper device are placed, and the height of the double scraper is set with a micrometer. The front blade is used to cast the slurry once, so that the slurry is initially spread on the casting base tape, and the distance between it and the casting base tape is 500μm. The rear blade is used to cast the slurry after spreading for a second time, in order to make the final single-layer casting film smoother and the grain arrangement more orderly, and the distance between it and the casting base tape is 500μm. The drying device of the casting machine is turned on and set to 50°C, and the appropriate initial speed of the casting machine is set. Then, the casting slurry is poured into the material trough. After the slurry is completely poured into the material trough, the forward rotation of the casting molding machine is turned on, so that the slurry is spread on the casting film base tape. After the casting is completed, wait for 5 to 10 minutes, and after the solvent of the casting film is dried, a single-layer casting film with a thickness of about 40μm is obtained.

[0113] Lamination is to laminate two single-layer cast films at 80°C and press them to make them fit tightly. Repeat the operation to laminate multiple cast films to a thickness of 2-3mm, then hot press at 70°C and 60MPa for 20min, and then perform cold isostatic pressing at 200MPa for 5min to obtain a cast film sheet. The purpose is to make the cast films fit more tightly and improve the density.

[0114] In combination with the second aspect, in some embodiments of the present invention, bismuth oxide is 3% of the molar fraction of the bismuth titanate template crystal.

[0115] In some comparative embodiments, the preparation method of the unmodified sodium bismuth titanate-based lead-free piezoelectric textured ceramic may be:

[0116] Bi2O3 and TiO2 were used as raw materials to synthesize Bi4Ti3O sheets by molten salt method. 12 Template crystal, its reaction equation is as follows:

[0117] 2Bi2O3+3TiO2→Bi4Ti3O12 .

[0118] Bismuth oxide and titanium dioxide are weighed and mixed in a molar ratio of 2:3.

[0119] The molten salt system selected a mixed molten salt of NaCl and KCl, and the mass ratio of the molten salt (NaCl and KCl) to the reaction raw materials (Bi2O3 and TiO2) was 1.5:1. Sodium chloride (NaCl) and potassium chloride (KCl) were dried in an oven for 24 hours before weighing. After the raw materials were mixed and subjected to ball milling, drying and calcination, bismuth titanate template crystals were obtained.

[0120] Bismuth oxide, titanium dioxide, sodium chloride, potassium chloride and anhydrous ethanol were placed in a ball mill and milled at a speed of 300 r / min for 4 h using a planetary ball mill. The mixed powder was dried, then loaded into a crucible and calcined in a muffle furnace. The temperature was raised to 1100°C at a rate of 5°C / min and kept warm for 2 h.

[0121] The bismuth oxide is 3% of the molar fraction of the bismuth titanate template crystal.

[0122] The additives include polyvinyl butyral, dibutyl phthalate, polyethylene glycol and castor oil, and the solvent is anhydrous ethanol, wherein the mass of the solvent accounts for 60% of the total mass of bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide and bismuth oxide, the mass of castor oil accounts for 2% of the total mass, the mass of polyvinyl butyral accounts for 9% of the total mass, and the mass of dibutyl phthalate accounts for 10% of the total mass.

[0123] Titanium dioxide, sodium carbonate, potassium carbonate, tantalum pentoxide, bismuth oxide, additives and solvent are mixed, ball-milled at a speed of 300 r / min for 12 hours, bismuth titanate template particles are added, and ball-milled at a speed of 250 r / min for 1-2 hours to obtain a mixed slurry.

[0124] Use a debubbler to debubble the mixed slurry, then lay a plastic film on the cast film base, assemble the cast film scraper device, place the material trough and scraper device, and use a micrometer to set the height of the scraper. The single blade is 150μm away from the cast film base. Turn on the drying device of the cast film machine and set it to 50℃, set the appropriate initial speed of the cast film machine, and then pour the cast film slurry into the trough. After the slurry is completely poured into the trough, turn on the forward rotation of the cast film forming machine to spread the slurry on the cast film base. After the casting is completed, wait for 5 to 10 minutes, and after the solvent of the cast film is dried, a single-layer cast film with a thickness of about 40μm is obtained.

[0125] Lamination is to laminate two single-layer cast films at 80°C and press them to make them fit tightly. Repeat the operation to laminate multiple cast films to a thickness of 2-3mm, then hot press at 70°C and 60MPa for 20 minutes, and then perform cold isostatic pressing at 200MPa for 5 minutes to obtain a cast film sheet. The purpose is to make the cast films fit more tightly and improve the density.

[0126] The debinding procedure is to heat the room temperature to 240°C for 120 minutes, then to 350°C for 270 minutes, then to 600°C for 500 minutes, keep the temperature for 80 minutes and then cool it in the furnace. The pressure of cold isostatic pressing is 200-250MPa, the duration is 5-10 minutes, and the green body is obtained after the second cold isostatic pressing.

[0127] The sintering was carried out in a double-layer alumina crucible using the method of burying homogeneous powder. The program was to heat up to 1150°C at a rate of 5°C / min and then keep the temperature for 8h.

[0128] The preparation of the sodium bismuth titanate-based lead-free piezoelectric random-oriented ceramics compared to the sodium bismuth titanate-based lead-free piezoelectric textured ceramics can be:

[0129] Using the traditional solid phase method, according to the chemical ratio [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3 Bismuth dioxide (Bi2O3), titanium dioxide (TiO2), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), strontium carbonate (SrCO3) and tantalum pentoxide (Ta2O5) are taken as raw materials, and ceramic powder is obtained through mixing, ball milling, drying, pre-sintering, secondary ball milling and secondary drying in sequence; a binder is added to the powder for granulation, and after preliminary tableting in a mold, the sample is isostatically pressed to compact it, and then debinding and sintering are carried out, and after cooling, sodium bismuth titanate-based lead-free piezoelectric random oriented ceramics are obtained.

[0130] Bismuth dioxide, titanium dioxide, sodium carbonate, potassium carbonate, strontium carbonate, tantalum pentoxide and a solvent are placed in a ball milling jar, and ball milled for 4 hours at a speed of 300 r / min using a planetary ball mill to obtain a slurry. The solvent is anhydrous ethanol.

[0131] The slurry was dried, put into a crucible and pre-calcined in a muffle furnace, heated to 850°C at a rate of 5°C / min and kept at this temperature for 3 h.

[0132] The pre-fired ceramic powder and solvent were placed in a ball mill, and ball milled at a speed of 300 r / min for 4 h using a planetary ball mill, and then dried and sieved.

[0133] The powder after the secondary ball milling was granulated by adding 6wt.% PVB alcohol solution as a binder, and the granulated powder was pressed into a tablet by a mold with a diameter of 10mm and a tablet press. The isostatic pressing process was performed by increasing the pressure to 200MPa for 5min, maintaining the pressure for 5min, and then reducing the pressure.

[0134] The sintering was carried out in a double-layer alumina crucible using the method of burying homogeneous powder. The program was to heat up to 1150°C at a rate of 5°C / min and then keep the temperature for 3h.

[0135] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0136] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0137] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.

[0138] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.

[0139] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0140] Example 1

[0141] Provided is a sodium bismuth titanate-based lead-free piezoelectric textured ceramic, the preparation method of which is as follows:

[0142] Step 1: Preparation of bismuth titanate template grains:

[0143] First, Bi2O3 and TiO2 are reacted according to the chemical reaction equation 2Bi2O3+3TiO2→Bi4Ti3O 12Formula calculations were performed, bismuth oxide and titanium dioxide were weighed and mixed in a molar ratio of 2:3, a single potassium chloride (KCl) molten salt was selected for the molten salt system, and the mass ratio of the molten salt (KCl) to the reaction raw materials (Bi2O3 and TiO2) was 1.5:1.

[0144] After weighing, place it in a ball mill, use zirconium oxide balls as grinding balls, anhydrous ethanol as solvent, and mix it in a planetary ball mill at 300r / min for 4h. The obtained slurry is dried at 80°C, and the powder obtained after drying is placed in a corundum crucible, covered with a crucible cover, and placed in a muffle furnace for synthesis to prevent the molten salt and Bi element from volatilizing in large quantities at high temperatures. The synthesis process is to heat to 1140°C at a heating rate of 5°C / min at room temperature for 8h, then cool to 300°C at a rate of 3°C / min and then cool with the furnace. The synthesized powder is added to deionized water at 80-100°C for stirring, dispersion and washing for multiple times. After pouring off the upper clear liquid, the powder in the beaker is finally dried to obtain the flaky Bi4Ti3O prepared under the pure KCl system. 12 Template grains.

[0145] Step 2: Preparation of sodium bismuth titanate-based lead-free piezoelectric textured ceramics with high electrostrain performance, the specific steps are as follows:

[0146] (1) Mixing

[0147] The required Bi4Ti3O 12 The template crystals, titanium dioxide (TiO2), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), strontium carbonate (SrCO3) and tantalum pentoxide (Ta2O5) were placed in an oven and dried at 150°C for 2 h. 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 The raw materials are weighed separately in the stoichiometric ratio of Bi:Na:K:Ti:Sr:Ta=0.48:0.3936:0.0864:0.994:0.04:0.006, and then the amount of substance is Bi4Ti3O 12 Template grains and 3% excess bismuth oxide (Bi2O3). Except for the BiT template grains, all other powders are placed in a nylon ball mill. Zirconia balls are used as grinding balls and anhydrous ethanol is used as solvent. After ball milling at a speed of 300r / min for 4h, take out and add Bi4Ti3O 124wt% castor oil with a total mass of 2% of TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3, 48wt% polyvinyl butyral (PVB) with a mass of 9% of the total mass, 40wt% dibutyl phthalate (DBP) with a mass of 10% of the total mass, and solvent was added again. The mass of the solvent added twice was Bi4Ti3O 12 , TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3, 60% of the total mass, was ball milled at 300r / min for 12h using a planetary ball mill. The obtained preliminary slurry was transferred into a beaker through a pipette, and the beaker was placed on a magnetic stirrer for stirring. Then, the flaky Bi4Ti3O prepared in the pure KCl system obtained in step 1 was added. 12 The template particles are stirred at room temperature for 1-2 hours to obtain a mixed slurry.

[0148] (2)Casting

[0149] Use a defoamer to defoam the mixed slurry until the slurry becomes viscous, then lay a plastic film on the cast base tape, assemble the double scraper device, place the material trough and scraper device, and use a micrometer to set the height of the double scraper. The distance between the front knife and the cast base tape is 500μm. The distance between the rear knife and the cast base tape is 500μm, and the distance between the front knife and the rear knife is 3cm. Turn on the drying device of the cast machine and set it to 50℃, set the initial speed of the cast machine to 0.2m / min, and then pour the cast slurry into the trough. After the slurry is completely poured into the trough, turn on the forward rotation of the cast molding machine to spread the slurry on the cast film base tape. After the casting is completed, wait for 5 to 10 minutes, and after the solvent of the cast film is dried, a single-layer cast film with a thickness of about 40μm is obtained.

[0150] (3) Lamination

[0151] Use a paper cutter to cut the cast film into a suitable size, raise the temperature of the hot press to 80°C, and put the sides of the two single-layer cast films without plastic film together. Use the hot press to press them tightly together, tear off the upper plastic film, and then put it together with the side of a cast film without plastic film. Repeat the operation to stack the cast films to a thickness of 2-3 mm to obtain a cast film laminate.

[0152] (4) Hot pressing, primary cold isostatic pressing

[0153] The cast film stack was placed in a hot press at 70°C and 60MPa for 15 minutes to make the layers in the green body more compact. After being taken out and cooled naturally, it was vacuum sealed and placed in a cold isostatic press for a cold isostatic pressing process. The sample was kept at a pressure of 200MPa for 5 minutes.

[0154] (4) Debinding and cold isostatic pressing

[0155] The green billet after hot pressing and cold isostatic pressing is cut into 7mm×7mm square regular small pieces and evenly placed on the alumina plate, and then pressed with the alumina plate. The sample is placed in the debinding furnace. The debinding process is to heat up to 240℃ for 120min at room temperature, then to 350℃ for 270min, and then to 600℃ for 500min, keep warm for 80min and cool with the furnace. After the cast film laminate is naturally cooled after debinding, the small piece is placed in a cold isostatic press after vacuum sealing for secondary cold isostatic pressing. The sample is kept at a pressure of 200MPa for 5min.

[0156] (6) Sintering

[0157] The sintering process was carried out in a double-layer alumina crucible and the debinding green body was placed in the crucible for sintering by using the method of burying homogeneous powder. The procedure was to heat the green body to 1150°C at a rate of 5°C / min and then keep the temperature for 8h to obtain sodium bismuth titanate-based lead-free piezoelectric textured ceramics, the chemical formula of which is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3, and named as textured ceramic-Sr 0.004 Ta 0.006 .

[0158] (7) Polishing, ultrasonic, silver plating, silver infiltration

[0159] After taking out, both sides of the sample need to be polished to remove the surface layer of the ceramic. Grind the ceramic to a thickness of 0.6-0.8mm, and use 600-mesh and 800-mesh diamond sandpaper for polishing. The polished ceramic surface should not be too smooth or too rough. After polishing, the sample is ultrasonically cleaned, taken out and dried for silver plating. Silver plating is to coat a layer of silver paste on the surface of the ceramic as an electrode to prepare for polarization and performance testing. After drying, the silver paste is evenly applied to both sides of the sample through screen printing technology, placed on a heating table for drying, and then placed in a box furnace for silver infiltration. The silver infiltration procedure is 720℃ for 15 minutes.

[0160] (8) Polarization

[0161] Before polarization, the silver paste on the edge of the ceramic piece needs to be polished away, leaving only the silver paste on the upper and lower surfaces to prevent the silver paste at the edge from conducting during polarization and causing a short circuit. Polarization is carried out in a silicone oil bath, and the polarization table consists of a high-voltage DC power supply and a constant temperature oil bath. Before polarization, the thickness of the ceramic piece is measured, and the voltage required for polarization is calculated using the electric field strength parameter of 3kV / mm. The voltage is slowly increased to the required voltage and maintained for 10 minutes to fully polarize the ceramic piece. If a sudden change in leakage current occurs during the polarization process accompanied by sparks, it means that the edge of the ceramic piece is turned on or the middle is broken down. The edge of the sample that is turned on or the broken-down part needs to be polished away, and then re-polarized. After the polarization is completed, a textured ceramic-Sr that can be tested is obtained. 0.004 Ta 0.006 .

[0162] Comparative Example 1

[0163] Provided is an unmodified sodium bismuth titanate-based lead-free piezoelectric textured ceramic, the preparation method of which is as follows:

[0164] Step 1: Preparation of bismuth titanate template grains:

[0165] First, Bi2O3 and TiO2 are reacted according to the chemical reaction equation 2Bi2O3+3TiO2→Bi4Ti3O 12 Formula calculation was performed, bismuth oxide and titanium dioxide were weighed and prepared according to a molar ratio of 2:3, and the molten salt system selected a mixed molten salt of sodium chloride (NaCl) and potassium chloride (KCl), and the mass ratio of molten salt (NaCl and KCl) to reaction raw materials (Bi2O3 and TiO2) was 1.5:1. After weighing, it was placed in a ball mill, with zirconium oxide balls as grinding balls and anhydrous ethanol as solvent, and mixed at 300r / min for 4h in a planetary ball mill. The obtained slurry was dried at 80°C, and the powder obtained after drying was placed in a corundum crucible, covered with a crucible cover and sealed and placed in a muffle furnace for synthesis to prevent the molten salt and Bi element from volatilizing in large quantities at high temperatures. The synthesis process is to heat to 1100°C at a heating rate of 5°C / min at room temperature for 8h, then cool to 300°C at a rate of 3°C / min and then cool with the furnace. The synthesized powder was added with deionized water at 80-100°C for stirring, dispersion and washing for many times. After the supernatant was discarded, the powder in the beaker was finally dried to obtain the flaky Bi4Ti3O prepared in the NaCl-KCl system. 12 Template grains.

[0166] Step 2: Preparation of unmodified sodium bismuth titanate-based lead-free piezoelectric textured ceramics, the specific steps are as follows:

[0167] (1) Mixing

[0168] The required Bi4Ti3O 12The template crystals, titanium dioxide (TiO2), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), strontium carbonate (SrCO3) and tantalum pentoxide (Ta2O5) were placed in an oven and dried at 150°C for 2 h. 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 The raw materials are weighed separately in the stoichiometric ratio of Bi:Na:K:Ti:Sr:Ta=0.48:0.3936:0.0864:0.994:0.04:0.006, and then the amount of substance is Bi4Ti3O 12 Template grains and 3% excess bismuth oxide (Bi2O3). Except for the BiT template grains, all other powders are placed in a nylon ball mill. Zirconia balls are used as grinding balls and anhydrous ethanol is used as solvent. After ball milling at a speed of 300r / min for 4h, take out and add Bi4Ti3O 12 4wt% castor oil with a total mass of 2% of TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3, 48wt% polyvinyl butyral (PVB) with a mass of 9% of the total mass, 40wt% dibutyl phthalate (DBP) with a mass of 10% of the total mass, and solvent was added again. The mass of the solvent added twice was Bi4Ti3O 12 , TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3, 60% of the total mass, was ball milled at 300r / min for 12h using a planetary ball mill. The obtained preliminary slurry was transferred into a beaker through a pipette, the beaker was placed on a magnetic stirrer for stirring, and then the flaky Bi4Ti3O prepared in the NaCl-KCl system prepared in step 1 was added. 12 The template particles are stirred at room temperature for 1-2 hours to obtain a mixed slurry.

[0169] (2)Casting

[0170] Use a debubbler to debubble the mixed slurry until the slurry becomes viscous, then lay a plastic film on the cast film base tape, assemble a single scraper device, place the material trough and scraper device, and use a micrometer to set the height of the double scraper. The single blade is 150μm away from the cast film base tape. Turn on the drying device of the cast film machine and set it to 50℃, set the initial speed of the cast film machine to 0.2m / min, and then pour the cast film slurry into the trough. After the slurry is completely poured into the trough, turn on the forward rotation of the cast film forming machine to spread the slurry flat on the cast film base tape. After the casting is completed, wait for 5 to 10 minutes, and wait for the solvent of the cast film to dry to obtain a single-layer cast film with a thickness of about 40μm.

[0171] (3) Lamination

[0172] Use a paper cutter to cut the cast film into a suitable size, raise the temperature of the hot press to 80°C, and put the sides of the two single-layer cast films without plastic film together. Use the hot press to press them tightly together, tear off the upper plastic film, and then put it together with the side of a cast film without plastic film. Repeat the operation to stack the cast films to a thickness of 2-3 mm to obtain a cast film laminate.

[0173] (4) Hot pressing, primary cold isostatic pressing

[0174] The cast film stack was placed in a hot press at 70°C and 60MPa for 15 minutes to make the layers in the green body more compact. After being taken out and cooled naturally, it was vacuum sealed and placed in a cold isostatic press for a cold isostatic pressing process. The sample was kept at a pressure of 200MPa for 5 minutes.

[0175] (4) Debinding and cold isostatic pressing

[0176] The green billet after hot pressing and cold isostatic pressing is cut into 7mm×7mm square regular small pieces and evenly placed on the alumina plate, and then pressed with the alumina plate. The sample is placed in the debinding furnace. The debinding process is to heat up to 240℃ for 120min at room temperature, then to 350℃ for 270min, and then to 600℃ for 500min, keep warm for 80min and cool with the furnace. After the cast film laminate is naturally cooled after debinding, the small piece is placed in a cold isostatic press after vacuum sealing for secondary cold isostatic pressing. The sample is kept at a pressure of 200MPa for 5min.

[0177] (6) Sintering

[0178] The sintering process was carried out in a double-layer alumina crucible and the debinding green body was placed in the crucible for sintering by using the method of burying homogeneous powder. The procedure was to heat the green body to 1150°C at a rate of 5°C / min and then keep the temperature for 8h to obtain sodium bismuth titanate-based lead-free piezoelectric textured ceramics, the chemical formula of which is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006 O3, and named as unmodified textured ceramic-Sr 0.004 Ta 0.006 .

[0179] (7) Polishing, ultrasonic, silver plating, silver infiltration

[0180] After taking out, both sides of the sample need to be polished to remove the surface layer of the ceramic. Grind the ceramic to a thickness of 0.6-0.8mm, and use 600-mesh and 800-mesh diamond sandpaper for polishing. The polished ceramic surface should not be too smooth or too rough. After polishing, the sample is ultrasonically cleaned, taken out and dried for silver plating. Silver plating is to coat a layer of silver paste on the surface of the ceramic as an electrode to prepare for polarization and performance testing. After drying, the silver paste is evenly applied to both sides of the sample through screen printing technology, placed on a heating table for drying, and then placed in a box furnace for silver infiltration. The silver infiltration procedure is 720℃ for 15 minutes.

[0181] (8) Polarization

[0182] Before polarization, the silver paste on the edge of the ceramic piece needs to be polished away, leaving only the silver paste on the upper and lower surfaces to prevent the silver paste at the edge from conducting during polarization and causing a short circuit. Polarization is carried out in a silicone oil bath, and the polarization table consists of a high-voltage DC power supply and a constant temperature oil bath. Before polarization, the thickness of the ceramic piece is measured, and the voltage required for polarization is calculated using the electric field strength parameter of 3kV / mm. The voltage is slowly increased to the required voltage and maintained for 10 minutes to fully polarize the ceramic piece. If a sudden change in leakage current occurs during the polarization process accompanied by sparks, it means that the edge of the ceramic piece is turned on or the middle is broken down. The edge of the sample that is turned on or the broken-down part needs to be polished away, and then re-polarized. After the polarization is completed, an unmodified textured ceramic-Sr is obtained for testing. 0.004 Ta 0.006 .

[0183] Comparative Example 2

[0184] Provided is a sodium bismuth titanate-based lead-free piezoelectric randomly oriented ceramic, the preparation method of which is:

[0185] (1) Powder preparation, ball milling and drying

[0186] Bismuth dioxide (Bi2O3), titanium dioxide (TiO2), sodium carbonate (Na2CO3), potassium carbonate (K2CO3), strontium carbonate (SrCO3) and tantalum pentoxide (Ta2O5) are used as raw materials. 0.5 (Na 0.82 K 0.18 ) 0.5 ] 0.96 Sr 0.04 Ti 0.994 Ta 0.006The raw materials are weighed separately according to the stoichiometric ratio of Bi:Na:K:Ti:Sr:Ta=0.48:0.3936:0.0864:0.994:0.04:0.006. Bi2O3, TiO2, Na2CO3, K2CO3, SrCO3, Ta2O5 are mixed and anhydrous ethanol is added as the ball milling solvent. The mixture is ball milled at a speed of 300r / min for 4h in a planetary ball mill. After the ball milling is completed, the zirconium balls and the slurry are poured into a porcelain plate and placed in an 80℃ oven for drying. At the same time, the oven door is opened to accelerate the evaporation of alcohol. After the drying is completed, the balls and the powder mixture are sieved through a 20-mesh sieve.

[0187] (2) Pre-burning

[0188] The sieved powder was placed in a corundum crucible and compacted lightly, and then placed in a muffle furnace and sintered at 850°C in air for 3 h.

[0189] (3) Secondary ball milling and drying

[0190] The sintered powder was added with anhydrous ethanol and ball-milled for a second time in a planetary ball mill at a speed of 300 r / min for 4 h. After ball-milling, the slurry was dried at 80° C. and passed through a 60-mesh sieve after drying.

[0191] (4) Granulation

[0192] After the second ball milling, add 6wt.% PVB alcohol solution as a binder to the obtained powder for granulation. Use a 3ml plastic pipette to measure PVB and add the powder drop by drop. 10ml PVB solution is required for every 10g of powder. In order to mix the powder and PVB evenly, add an appropriate amount of anhydrous ethanol for grinding. After drying, pass through a 20-mesh sieve to obtain particles of appropriate size.

[0193] (5) Tableting, cold isostatic pressing

[0194] Use a 10mm diameter mold and tablet press for tableting. Weigh 0.35g of powder with good fluidity each time and pour it into the steel mold. Slowly pressurize to 10MPa and maintain the pressure for 60s to obtain a disc sample with a diameter of 10mm and a thickness of 1.0mm. Put the disc sample into a sealing bag, seal it with a vacuum sealer, and then put it into a cold isostatic press at a pressure of 200MPa for 5min to further compact the disc.

[0195] (6) Debonding

[0196] The cold isostatically pressed wafers were placed in a binder removal furnace, slowly heated to 600°C for 60 minutes and then cooled down along with the furnace.

[0197] (7) Sintering

[0198] The sample after debinding was placed in a crucible, and the pre-sintered powder was embedded in the upper and lower surfaces of the sample for powder embedding treatment. The crucible was covered with a lid, and then placed in a muffle furnace and heated to 1150°C at a rate of 3-5°C / min and then kept warm for 3h for sintering. The sample was cooled to room temperature with the furnace to obtain sodium bismuth titanate-based lead-free piezoelectric randomly oriented ceramics, named randomly oriented ceramics-Sr 0.004 Ta 0.006 .

[0199] (8) Polishing, ultrasonic, silver plating, silver infiltration

[0200] After taking out, both sides of the sample need to be polished to remove the surface layer of the ceramic. The thickness of the ceramic is ground to 0.6-0.8mm, and 600-mesh and 800-mesh diamond sandpaper are used for polishing. After polishing, the sample is ultrasonically cleaned, taken out and dried for silver plating. After drying, the silver paste is evenly applied to both sides of the sample through screen printing technology, placed on a heating table for drying, and then placed in a box furnace for silver infiltration. The silver infiltration procedure is to keep warm at 720℃ for 15min, cool naturally, and obtain a silver-plated randomly oriented ceramic sample. After applying 3kV / mm voltage polarization at room temperature, a randomly oriented ceramic-Sr that can be tested is obtained. 0.004 Ta 0.006 .

[0201] Characterization and performance testing of ceramics in Experimental Example 1

[0202] The three materials prepared in Example 1 and Comparative Example 1 (sheet-shaped Bi4Ti3O prepared in pure KCl system) 12 Template grains, Bi4Ti3O flakes prepared in NaCl-KCl system 12 Template grains, textured ceramics for testing - Sr 0.004 Ta 0.006 , unmodified textured ceramics available for testing - Sr 0.004 Ta 0.006 , Randomly oriented ceramics available for testing - Sr 0.004 Ta 0.006 ) is a sample, and the following characteristics or performance tests are performed:

[0203] (1) Physical structure characterization

[0204] The four materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 (sheet-shaped Bi4Ti3O prepared in pure KCl system) 12 Template grains, textured ceramics for testing - Sr 0.004 Ta 0.006 , unmodified textured ceramics available for testing - Sr 0.004 Ta 0.006 , Randomly oriented ceramics available for testing - Sr 0.004Ta 0.006 ) for phase structure characterization.

[0205] In this experiment, an X-ray diffractometer (D8Advance) was used to measure the XRD patterns of the samples. Figure 1 As shown, the crystal structure, phase composition and texture degree of the textured ceramic can be analyzed from the XRD spectrum. The scanning angle range is between 10° and 80°, and the test step is 0.05°. The obtained XRD spectrum is used to calculate the texture degree of the textured ceramic in the <00l> direction through the Lotgering factor formula. Figure 1 All diffraction peaks are consistent with the standard PDF card of BiT (PDF#72-1019), and no diffraction peaks of the second phase are found in the sample, indicating that pure phase BiT template grains can be obtained by using KCl as molten salt under the condition of keeping at 1140℃ for 8h.

[0206] like Figure 2 and Figure 3 As shown, compared with the randomly oriented ceramics, the prepared textured ceramic-Sr 0.004 Ta 0.006 The {200} diffraction peak intensity is significantly enhanced, and the textured ceramic grains are <001> Orientation, calculated, improved texture ceramic-Sr 0.004 Ta 0.006 The texture degree of unmodified ceramic-Sr 0.004 Ta 0.006 Compared with the improved textured ceramic-Sr 0.004 Ta 0.006 The emergence of new impurities indicates that the template grains sintered in the mixed salt NaCl-KCl system may contain Na 0.5 Bi 8. 5Ti7O 27 , tape casting will produce textured ceramics with a stoichiometric ratio shift, affecting the performance of the sample.

[0207] (2) Scanning electron microscopy (SEM) characterization

[0208] The materials prepared in Example 1 and Comparative Example 1 (flaky Bi4Ti3O prepared in pure KCl system) 12 Template grains, Bi4Ti3O flakes prepared in NaCl-KCl system 12 Template grains, Bi4Ti3O flakes prepared in NaCl-KCl system 12 Template grains, improved textured ceramics-Sr 0.004 Ta 0.006 ) was used to characterize the physical structure. In this experiment, a desktop scanning electron microscope (TM4000Plus) was used to photograph the surface and cross section of the ceramic samples.

[0209] like Figure 4 and Figure 5 As shown, the flake Bi4Ti3O prepared in pure KCl system 12 Template grains and flake Bi4Ti3O prepared in NaCl-KCl system 12 The template grains are all flaky and the crystallization is relatively complete. By measuring the width and thickness of the flaky crystals in the SEM image and calculating their directional ratio L / D (the ratio of the average length in the horizontal direction to the average thickness in the vertical direction), it can be seen that the radial length of the template grains synthesized in the KCl molten salt system is 9-20μm and the thickness is about 0.3μm; the template grain size synthesized in the NaCl-KCl molten salt system is 5-11μm and the thickness is about 0.35μm. The former has a larger directional ratio than the latter and is more suitable for tape casting. Figure 6 It can be seen that the improved textured ceramic has good grain growth, clear and obvious boundaries, the crystal grains are stacked layer by layer like bricks, and the grain size grows along the template direction.

[0210] Figure 6 This is a microscopic morphology of the cross section of the textured ceramic prepared in Example 1. Figure 6 It can be seen that the grains grow well, with clear and obvious boundaries, and the crystal grains are stacked like bricks. Because the template grains engulf the surrounding raw materials and react during the sintering process, the grain size is large and grows along the template direction. Inside the ceramic, the arrangement of the grains is still in the same direction and in block shape, but there are inevitably some gaps between the grains. On the one hand, this is because the textured ceramics are made by lamination and hot pressing, and more additives need to be added during the preparation process, and it is impossible to achieve the same density as the traditional solid phase method; on the other hand, because the grain size of the textured ceramics is large, some gaps will remain between the grains during the growth process, and it cannot be completely densified. However, it can also be seen that the ceramic texture is good, indicating that the selected template grains are suitable for the component ceramics, and the casting and hot pressing processes are good.

[0211] (3) Electrostrain performance test

[0212] The materials prepared in Example 1 and Comparative Example 1 (improved textured ceramic-Sr 0.004 Ta 0.006 , unmodified ceramic-Sr 0.004 Ta 0.006 ) to test the electrostrain performance. This experiment uses a ferroelectric and strain test bench (AirACCTTF-2000) to measure the electrostrain performance of the sample under an alternating electric field. The results of Example 1 are shown in Figure 7 As shown, the results of Comparative Example 1 are as follows Figure 8 shown.

[0213] like Figure 7As shown in the figure, when the Sr content is 0.004 and the Ta content is 0.006, the improved texture ceramic-Sr 0.004 Ta 0.006 The maximum unipolar strain reaches 1.12%@6kV / mm. Figure 8 As shown, the unmodified textured ceramic-Sr 0.004 Ta 0.006 The unipolar strain is 0.37%@6kV / mm. Combined with the phase structure characterization results, it can be seen that the present invention introduces Sr into the A position of the two-component solid solution system of sodium bismuth titanate-potassium bismuth titanate (BNT-BKT). 2+ and B position introduces Ta 5+ Ion doping modification of A and B positions combined with an improved tape-casting process can improve the texture and purity of the ceramic, thereby improving the electrostrain performance.

[0214] The present invention provides a method for preparing a sodium bismuth titanate-based lead-free piezoelectric textured ceramic with excellent electrostrain performance, by introducing Sr into the A position of a sodium bismuth titanate-potassium bismuth titanate (BNT-BKT) two-component solid solution system. 2+ and B position introduces Ta 5 + Ions were used for common ion doping modification at the A and B positions, and bismuth titanate template grains with high purity, large size and large orientation ratio were prepared in a single molten salt system of KCl by the molten salt method. Then, the reaction template grain growth method was used to improve the ratio of the casting slurry, set up a double casting knife, and use a secondary isostatic pressing process and a primary hot pressing process, and finally a dense sample with higher purity and better electrostrain performance than the unmodified textured ceramics was obtained. This method is simple in process, easy to operate, and low in cost. It can save experimental costs and equipment investment, and has good practical prospects in the field of electrostrain materials.

[0215] It should be noted that the present invention utilizes a single molten salt system of KCl, sintered at 1140°C in a muffle furnace, and the insulation time is 8 hours to prepare the flaky BiT template grains, which have the advantages of high purity, large size, and large orientation ratio. They can be "laid flat" in the cast film under the action of a casting scraper, and are more suitable for casting than the template grains prepared in the NaCl-KCl mixed molten salt system.

[0216] Furthermore, the present invention uses a double casting scraper device to perform secondary casting on the slurry, so that the final single-layer casting film is smoother, the grain arrangement is more orderly, and the texture degree of the textured ceramic is improved.

[0217] Furthermore, the invention is innovative in the formulation of the tape casting slurry, and only three kinds of glue are added as additives, and the mass of Bi4Ti3O 12, TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3, 4wt% castor oil, 9wt% polyvinyl butyral (PVB), 40wt% dibutyl phthalate (DBP), 10wt% of the total mass, and the mass of the solvent added twice was Bi4Ti3O 12 , TiO2, Na2CO3, K2CO3, Ta2O5, SrCO3 and Bi2O3 account for 60% of the total mass, saving process costs while obtaining the slurry with the most suitable fluidity and ductility for tape casting.

[0218] Furthermore, the A-site of the two-component solid solution system ceramic of sodium bismuth titanate-potassium bismuth titanate (BNT-BKT) is substituted by Sr doping, and the B-site of the system is substituted by Ta doping. The co-doping of Sr2+ and Ta4+ will lead to the formation of cationic vacancies inside the lattice, destroying the long-range order of the ferroelectric in the piezoelectric ceramic, making the electric domain easier to turn, and the relaxation phase gradually transforms into the ferroelectric phase in the process of increasing the external electric field, thereby improving the piezoelectric performance.

[0219] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A sodium bismuth titanate-based lead-free piezoelectric textured ceramic, characterized in that: The chemical composition is [Bi 0.5 (Na 0.82 K 0.18 ) 0.5 0.96 Sr 0.04 Ti 1-x Ta x O3, 0 < x < 0.01, and the texture degree of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic is > 90%.​ 2. The sodium bismuth titanate-based lead-free piezoelectric textured ceramic according to claim 1, characterized in that: The textured ceramic grains of the sodium bismuth titanate-based lead-free piezoelectric textured ceramic are <001> orientation.

3. A method for preparing the sodium bismuth titanate-based lead-free piezoelectric textured ceramic according to claim 1 or 2, characterized in that: The steps include: Bismuth titanate template crystals are prepared by a single molten salt system. According to the chemical composition, the bismuth titanate template crystals, titanium dioxide, sodium carbonate, potassium carbonate, strontium carbonate and tantalum pentoxide are weighed and mixed with bismuth oxide, additives and solvents to obtain a ceramic slurry. The ceramic slurry is tape-casted by a reactive template grain growth method through a tape-casting process to obtain a single-layer tape-cast film. The single-layer tape-cast films are stacked to obtain a tape-cast membrane sheet. The tape-cast membrane sheet is sequentially subjected to hot pressing, primary cold isostatic pressing, debinding, secondary cold isostatic pressing and sintering to obtain the sodium bismuth titanate-based lead-free piezoelectric textured ceramic.

4. The method according to claim 3, characterized in that The preparation method of the bismuth titanate template crystal comprises the following steps: after mixing Bi2O3 and TiO2, adding a single molten salt, and after ball milling, drying and calcining, obtaining the bismuth titanate template crystal.

5. The method according to claim 3, characterized in that: The additives include polyvinyl butyral, dibutyl phthalate, polyethylene glycol and castor oil.

6. The method according to claim 3, characterized in that The stacking method comprises: laminating and pressing two single-layer cast films at 70-80° C. to make them closely fit, and repeating the operation to stack multiple cast films to a thickness of 2-3 mm.

7. The method according to claim 3, characterized in that The hot pressing comprises: hot pressing at 60-80° C. and 50-60 MPa for 15-20 min.

8. The method according to claim 3, characterized in that The debinding procedure includes: heating to 240° C. for 120 minutes at room temperature, heating to 350° C. for 270 minutes, and heating to 600° C. for 500 minutes, keeping the temperature for 80 minutes, and then cooling with the furnace.

9. The method according to claim 3, characterized in that: The primary cold isostatic pressing comprises: maintaining pressure at 200-250 MPa for 5-10 min; and / or, the secondary cold isostatic pressing comprises: maintaining pressure at 200-250 MPa for 5-10 min.

10. The method according to claim 3, characterized in that The sintering comprises: heating to 1150° C. at a rate of 3-5° C. / min and then keeping the temperature for 8 hours.

Citation Information

Patent Citations

  • Sheet bismuth sodium titanate mould plate grain and manufacture method thereof

    CN101244933A

  • Textured (1-x-y) BNT-xBKT-yKNN ceramic material and preparation method thereof

    CN102503413A

  • High electrostrictive leadless piezoelectric ceramic material and preparation method therefor and application thereof

    CN105130419A

  • Sodium bismuth titanate-based leadless piezoelectric textured ceramic with high texture degree and high electrostrictive strain performance and preparation method of sodium bismuth titanate-based leadless piezoelectric textured ceramic

    CN115196961A

  • Crystal-oriented ceramics and methods for producing the same

    EP0826643A1